Directed transport of neutrophil-derived extracellular vesicles enables platelet-mediated innate immune response - Rossaint, Jan; Kühne, Katharina; Skupski, Jennifer; Van Aken, Hugo; Looney, Mark R.; Hidalgo, Andres; Zarbock, Alexander (Nature communications, 2016)
The innate immune response to bacterial infections requires the interaction of neutrophils and platelets. Here, we show that a multistep reciprocal crosstalk exists between these two cell types, ultimately facilitating neutrophil influx into the lung to eliminate infections. Activated platelets adhere to intravascular neutrophils through P-selectin/P-selectin glycoprotein ligand-1 (PSGL-1)-mediated binding, a primary interaction that allows platelets glycoprotein Ibα (GPIbα)-induced generation of neutrophil-derived extracellular vesicles (EV). EV production is directed by exocytosis and allows shuttling of arachidonic acid into platelets. EVs are then specifically internalized into platelets in a Mac1-dependent fashion, and relocated into intracellular compartments enriched in cyclooxygenase1 (Cox1), an enzyme processing arachidonic acid to synthesize thromboxane A 2 (TxA 2 ). Finally, platelet-derived-TxA 2 elicits a full neutrophil response by inducing the endothelial expression of ICAM-1, intravascular crawling, and extravasation. We conclude that critical substrate–enzyme pairs are compartmentalized in neutrophils and platelets during steady state limiting non-specific inflammation, but bacterial infection triggers regulated EV shuttling resulting in robust inflammation and pathogen clearance. Interaction between platelets and neutrophils promotes neutrophil activation. Here the authors show that neutrophils initiate the cross-talk with platelets by shuttling arachidonic acid via extracellular vesicles, which platelets convert to thromboxane A 2 that then elicits neutrophil activation.